Nonlinear absorption tuning by composition control in bimetallic plasmonic nanoprism arrays. Issue 29 (1st July 2015) - Cesca, Tiziana; Michieli, Niccolò; Kalinic, Boris; Sánchez-Espinoza, Ana; Rattin, Marco; Russo, Valentina; Mattarello, Valentina; Scian, Carlo; Mazzoldi, Paolo; Mattei, Giovanni
Abstract : The nonlinear absorption properties of Au–Ag bilayered triangular nanoprism arrays can be tuned by controlling the nanoprism bimetallic composition. Abstract : The nonlinear absorption properties of bidimensional arrays of Au–Ag bilayered nanoprisms have been investigated by z -scan measurements as a function of the bimetallic nanoprism composition. A tunable ps laser system was used to excite the ultrafast, electronic nonlinear response matching the laser wavelength with the quadrupolar surface plasmon resonances, in the visible range, of each nanoprism array. Due to the strong electromagnetic field confinement effects at the nanoprism tips, demonstrated by finite element method simulations, these nanosystems proved to have enhanced nonlinear optical properties. Moreover, a tunable changeover from reverse saturable absorption (RSA) to saturable absorption (SA) can be obtained by properly controlling the bimetallic composition of the nanoprisms, without modifying the overall morphology of the nanosystems. This capability makes these nanosystems extremely interesting for the realization of solid-state nanophotonic devices with enhanced ultrafast nonlinear optical properties.